PENGARUH MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENULIS TEKS DEKRIPSI SMP NEGERI 7 SUNGAI RAYA - Liliy Erlinda Purnama Sari; Nanang Heryana; Ahmad Rabi’ul Muzammil (Universitas Tanjungpura, 2020)
AbstractThis study aims to analyze and describe the effect of using audiovisual media on students’ writing skills in the descriptive text at class VII of SMPN 7 Sungai Raya. The research method implemented in this study was an experiment in the form of a quasi-experimental with nonequivalent control group design. The data was gathered using a pretest and posttest. The population in this study was the class VII students of SMPN 7 Sungai Raya. The samples were students in class VII B as an experiment group and VII C as the control group, which was taken using a purposive sampling technique. The findings showed that the average score of the control class and experiment class was 65.17 and 82.00. In the t-test, tcount was -7.293, and the ttable with was -2.048 and Sig (0.000)(0.05). The tcount value was located far from the ttable and thus being out of the H0 rejection area. Hence, the selected learning media is more effective in improving the students’ writing skills in descriptive text than using a conventional method. Keywords: Audio-Visual Media, Descriptive Text, Writing Skill.